REMEDIASI MISKONSEPSI SISWA DENGAN MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE (CLIS) BERBANTUAN SIMULASI PhET - Iryani, Iryani; Tandililing, Edy; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study was conducted to determine the effectiveness of Children Learning In Science (CLIS) model using PhET simulation to reduce students misconception on hydrostatic pressure in SMPN 7 Pontianak.  This study was quasi  pre-experimental design with one group pre-test post-test design. The population of this study was ninth grade  students in SMPN 7 Pontianak. Intact group random sampling was used that involving IX F. the average decrease of student misconceptions were 38,03% with significant conceptual change by Mc Nemar test ( ). There was significant conceptual change after remediation by apply CLIS model using PhET simulation to reduce students misconception on hydrostatic pressure. Result reveal that the effectiveness level was 0,67 (medium). This research is expected to be used as an alternative remediation activities to reduce misconception in learning process and improve student’s learning outcomes.   Keywords: Misconception, CLIS, PhET, Hydrostatic Pressure